2014
DOI: 10.1002/ajpa.22513
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of multiple data types from the bering strait region: Cranial and dental metrics and nonmetrics, mtDNA, and Y‐chromosome DNA

Abstract: Different data types have previously been shown to have the same microevolutionary patterns in worldwide data sets. However, peopling of the New World studies have shown a difference in migration paths and timings using multiple types of data, spurring research to understand why this is the case. This study was designed to test the degree of similarity in evolutionary patterns by using cranial and dental metric and nonmetric data, along with Y-chromosome DNA and mtDNA. The populations used included Inuits from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 89 publications
1
35
0
2
Order By: Relevance
“…The correlation between autosomal SNP and cranial non-metrics matrices is also fairly high in both cases but does not reach significance. This is in agreement with the results of some previous works showing a certain correspondence between cranial non-metric and genetic data (Ricaut et al, 2010: Herrera et al, 2014.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The correlation between autosomal SNP and cranial non-metrics matrices is also fairly high in both cases but does not reach significance. This is in agreement with the results of some previous works showing a certain correspondence between cranial non-metric and genetic data (Ricaut et al, 2010: Herrera et al, 2014.…”
Section: Discussionsupporting
confidence: 93%
“…More generally, correlations between intergroup neutral genetic distances and those based on cranial morphology have been the focus of many studies (Roseman, 2004;Gonzalez-Jose et al, 2004;Relethford, 2004;Roseman and Weaver, 2007;Smith, 2009;von Cramon-Taubadel, 2009b;Relethford, 2010;Herrera et al, 2014). But there are several important issues which require further consideration and that are related to both genetic and morphometric data used in such studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent publications also examine the agreement between paired genetic and morphological data using archaeological samples. First, Ricaut et al (2010) examined mixed cranial and dental morphology samples to estimate kinship within a single site, while Herrera et al (2014) examined cranial metric and morphological variation to understand population history at a regional level. Both acknowledge the value of skeletal variants in bioarchaeological studies at these geographic scales.…”
Section: " "mentioning
confidence: 99%
“…Ricaut et al (2010) found that combined morphological data provided good resolution in identifying pairs of kin within a Mongolian necropolis, although genetic findings detected double the number. In the second study, Herrera et al (2014) compared Y-chromosome, mtDNA, cranial metric, and cranial morphology data in samples from the Bering Strait region; they found that craniometric distances were correlated with mtDNA, while distances based on cranial morphology were correlated with those from Ychromosome variants. Viewed as a whole, two lessons can be learned from the present and previous studies: 1) additional work needs to be undertaken to determine which skeletal and genetic data are best suited to answer particular research questions (Herrera et al, 2014;present study); and 2) care should be taken when formulating very fine scale interpretations of population history from skeletal data (Ricaut et al, 2010;present study;also Scott and Turner, 1997).…”
Section: " "mentioning
confidence: 99%